Respuesta :

Answer:

1. (52 - 2) (1 + 1) = 100

2. (12 - 2) (9 + 1) = 100

3. (6 - 2) (24 + 1) = 100

4. (3 - 2) (99 + 1) = 100

5. (102 - 2) (0 + 1) = 100

Step-by-step explanation:

1. let r= 52 and s= 1

(52 - 2) (1 + 1) = 100

50 × 2 = 100

2. let r= 12 and s= 9

(12 - 2) (9 + 1) = 100

10 × 10 = 100

3. let r= 6 and s= 24

(6 - 2) (24 + 1) = 100

4 × 25 = 100

4. let r= 3 and s= 99

(3 - 2) (99 + 1) = 100

1 × 100 = 100

5. let r= 102 and s= 0

(102 - 2) (0 + 1) = 100

100 × 1 = 100

[tex]\tt{ \green{P} \orange{s} \red{y} \blue{x} \pink{c} \purple{h} \green{i} e}[/tex]

ACCESS MORE